Chat with our AI personalities
1 1 2 3 5 etc start with 1 and 1 and to get the 3rd term 1+1 = 2 add 2nd and 3rd term to get 4th --- 1 + 2 = 3 add 3rd and 4th term to get the 5th --- 2 + 3 = 5 etc
You start with the number 4, then multiply with the "common ratio" to get the next term. That, in turn, is multiplied by the common ratio to get the next term, etc.
recursive rule: term(n+1) = term(n) + (n) also, n starts at 0 and term(1)=3 term(1) = 3 ; (n=0) term(2) = term(1) + (1) = 4 term(3) = term(2) + (2) = 6 term(4) = term(3) + (3) = 9 term(5) = term(4) + (4) = 13 . . .
There are 3 syllables. Wa-ri-ly.
If you notice, there is a common difference between the terms: tn - tn-1 = -4 So the nth term is: tn = tn-1 - 4 For this recursive sequence to be defined though, you need something to start with as your tn-1. So start with t1= 3 and you're done.